Hubungan Karakteristik dan Motif dengan Efek Media Kasus Ibu Rumah Tangga Pendengar Acara Pro Dokter di Pro 2 LPP RRI Jakarta - Agustini .; S. Hamdani N; K. Matindas (Institut Pertanian Bogor, 2009)
The aims of this study were to analyze the housewives characteristics, the motivation for listening to Pro Doctorradio program, the relationship between characteristics and motivation, the relationship between media use andmotivation, and the relationship between motivation and satisfaction as the effect of the media. The study wasdesigned as a survey employing a descriptive correlational method. One hundred housewives were chosen asrespondents through a simple random sampling method. Data were analyzed with Rank Spearman Test, Chi SquareTest and Contingency Coefficient Test using SPSS program. Results of the study show the characteristics of samplesas follows: average age is 37 years, without occupation, family income is between Rp1-2 million, senior high school(or equivalent) education, and between 1 to 3 children in the family. The motivations for listening to the radioprogram are: gaining information, broadening vision, easiness to solve problems in health, feeling more secure,confidence, and having a topic to talk about when meeting friends. Family income correlates highly significantly withmotives for: gaining information, broadening vision, and having a topic to talk about; while correlates significantlywith motives for easiness to solve problems, and confidence. The number of family members has a high significantrelationship with motives for gaining information, has significant relationship with motivation for having a topic totalk about. There are significant differences in any motivation between housewives who have occupations and thosewho do not have one. There is a strong relationship between occupation and the motivation for: solving problems,feeling more secure, confidence, having a topic to talk about, entertainment, feeling spare time, and routinines. Thefrequency to listen correlates highly significantly with motivation for: gaining information, while correlatessignificantly with feeling spare time and routines. The intensity of completeness, active sums/phone is closelyassociated with the motivation to fill spare time, the associated with health problems, and rout nines. Motivation for:rout nines and having topic to talk about, correlate significantly with the cognitive and conative aspects. Motivationfor: gaining information and broadening vision correlate highly significantly with the affective and connate aspects.